EFEKTIVITAS PSIKOEDUKASI BERBASIS MINI DRAMA DALAM MENINGKATKAN PEMAHAMAN TERHADAP BULLYING PADA SISWA SEKOLAH DASAR - Grin Rayi Prihandini; Sitti Rahmah Marsidi; Jatayu Hadi Prakoso; Lisna Hikmawaty (Universitas Mataram, 2026)
Elementary school is the formal education children receive after their family environment. At this age, children begin to develop their self-concept and it influences how they socialize with others. In the school environment, children begin to socialize through friendships with peers. Within these friendships, potential conflicts arise, and the resulting behavior can lead to bullying. Bullying cases occurring in elementary schools require attention because the psychological impacts can disrupt optimal individual development, even into adulthood. Therefore, an intervention program is needed to address this issue. This activity aims to improve elementary school students' understanding of bullying and prevent such behavior. The activity involved 31 students in grades 1-3 at SDIT Global Prima, Bekasi. The activity took the form of psychoeducation through mini-dramas and discussions related to bullying. The Wilcoxon Signed-Rank Test results showed a significant difference between pretest and posttest scores regarding understanding of bullying (Z = -3.286, p < 0.05). The mean rank value indicated that 19 participants experienced an increase in their pretest-posttest scores. This means that most participants showed an increase in their scores after the intervention. An effect size of 0.59 indicates that the intervention had a moderate impact. This indicates that the mini-drama-based psychoeducational activity had a significant practical impact on improving students' understanding of bullying. Overall, these findings support the effectiveness of the intervention in preventing bullying by strengthening students' understanding.